Expansion of adipose mesenchymal stromal cells is affected by human platelet lysate and plating density - Cholewa, Dominik; Stiehl, Thomas; Schellenberg, Anne; Bokermann, Gudrun; Joussen, Sylvia; Koch, Carmen; Walenda, Thomas; Pallua, Norbert; Marciniak-Czochra, Anna; Suschek, Christoph V.; Wagner, Wolfgang (Cell transplantation, 2011)
The composition of mesenchymal stromal cells (MSCs) changes in the course of in vitro culture expansion. Little is known how these cell preparations are influenced by culture media, plating density, or passaging. In this study, we have isolated MSCs from human adipose tissue in culture medium supplemented with either fetal calf serum (FCS) or human platelet lysate (HPL). In addition, culture expansion was simultaneously performed at plating densities of 10 or 10,000 cells/cm2. The use of FCS resulted in larger cells, whereas HPL significantly enhanced proliferation. Notably, HPL also facilitated expansion for more population doublings than FCS (43 ± 3 vs. 22 ± 4 population doubling; p < 0.001), while plating density did not have a significant effect on long-term growth curves. To gain further insight into population dynamics, we conceived a cellular automaton model to simulate expansion of MSCS. It is based on the assumptions that the number of cell divisions is limited and that due to contact inhibition proliferation occurs only at the rim of colonies. The model predicts that low plating densities result in more heterogeneity with regard to cell division history, and favor subpopulations of higher migratory activity. In summary, HPL is a suitable serum supplement for isolation of MSC from adipose tissue and facilitates more population doublings than FCS. Cellular automaton computer simulations provided additional insights into how complex population dynamics during long-term expansion are affected by plating density and migration.
Gesehen am 29.06.2022